Optimizing clonidine dosage for sedation in mechanically ventilated children: A pharmacokinetic simulation study. Issue 10 (26th August 2019) - Hayden, John C.; Bardol, Maddlie; Doherty, Dermot R.; Dawkins, Ian; Healy, Martina; Breatnach, Cormac V.; Gallagher, Paul J.; Cousins, Gráinne; Standing, Joseph F.
Abstract: Background: Clonidine is in widespread off‐label use as a sedative in mechanically ventilated children, despite limited evidence of efficacy. A variety of dosage regimens have been utilized in clinical practice and in research studies. Within these studies, clonidine has inconsistently shown useful sedation properties. One of the reasons attributed to the inconsistent signs of efficacy is suboptimal clonidine dosing. Aims: This study aims to propose a target plasma concentration and simulate clonidine pharmacokinetics (PK) in a cohort of mechanically ventilated children to evaluate the adequacy of clonidine dosage regimens used in clinical practice and research studies. Methods: A literature search was undertaken to identify a clonidine pharmaockinetic‐pharmacodynamics (PKPD) model, from which a target concentration for sedation was defined. Using a previously published PK model, the projected plasma concentrations of 692 mechanically ventilated children (demographics taken from a recent study) were generated. Doses from recently published clinical studies were investigated. Adequacy of each regimen to attain therapeutic clonidine plasma concentrations was assessed. Results: A target plasma concentration of above 2 µg/L was proposed. Nine dosage regimens (four intravenous boluses, four intravenous infusions, and one nasogastric route boluses) were evaluated ranging from 1 µg/kg eight hourly intravenous boluses to a regimen up to 3 µg/kg/hr continuous intravenous infusion. Regimens with a loading dose of 2 µg/kg followed by variable continuous infusion of up to 2 µg/kg/hr titrated according to sedation score appear most suitable. Doses should be halved in neonates. Conclusion: The variety of dosage regimens in the previous studies of clonidine along with difficulties in the conduct of interventional studies may have contributed to the lack of efficacy data to support its use. Simulations of clonidine plasma concentrations based on known population pharmacokinetic parameters suggest a loading dose followed by higher than current practice maintenance dose infusion is required to achieve adequate steady‐state concentrations early in treatment. Further PKPD studies will aid in the determination of the optimal clonidine dosage regimen.